2014
DOI: 10.1002/iid3.35
|View full text |Cite
|
Sign up to set email alerts
|

MHC‐Ig induces memory T cell formationin vivoand inhibits tumour growth

Abstract: Induction of a T cell mediated immune response is critical for the eradication of viral infections and tumours. Soluble peptide-loaded major histocompatibility complex-Ig (pep−MHC-Ig) have been shown to bind their cognate ligands, T cell receptor, with high affinity, and are successfully used to visualize antigen-specific T cells. Furthermore, immobilized pep−MHC-Ig can activate and expand antigen-specific T cells in vitro and in vivo. In this study, we investigate the use of pep−MHC-Ig as a potential strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 36 publications
(52 reference statements)
2
9
0
Order By: Relevance
“…If SVY is indeed a cross-reactive antigen, one should be able to immunize mice and test for cross-reactive responses in vivo. Immunization of Bifidobacterium-negative Taconic mice with SVY-loaded K b complexes, as previously described (14), led to approximately 60% killing of SVY target cells in vivo and a cross-reactive killing of approximately 50% of SIY-pulsed targets in vivo ( Figure 4E). This was associated with an increased number of K b SVY effector T cells, from 0.4% to 0.6% ( Figure 4F and Supplemental Figure 9C).…”
Section: B Breve Contains a Peptide Epitope (Svy) That Is Homologoussupporting
confidence: 70%
See 1 more Smart Citation
“…If SVY is indeed a cross-reactive antigen, one should be able to immunize mice and test for cross-reactive responses in vivo. Immunization of Bifidobacterium-negative Taconic mice with SVY-loaded K b complexes, as previously described (14), led to approximately 60% killing of SVY target cells in vivo and a cross-reactive killing of approximately 50% of SIY-pulsed targets in vivo ( Figure 4E). This was associated with an increased number of K b SVY effector T cells, from 0.4% to 0.6% ( Figure 4F and Supplemental Figure 9C).…”
Section: B Breve Contains a Peptide Epitope (Svy) That Is Homologoussupporting
confidence: 70%
“…Immunization assay. Recipient mice were injected intraperitoneally with 10 μg/mouse of anti-CD40 mAb (clone 3/23; BioLegend) and a day later immunized subcutaneously with 250 μg as indicated of either OVA− K b -Ig or SVY− K b -Ig dimer (14).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it could be demonstrated that anti-CD40 mAb induced maturation of APC prior to pMC immunization was crucial for an effective immune response. Administration of anti-CD40 mAb together with or after pMC administration did not result in formation of a robust immune response, which further supports that the pMC is presented on the cell surface and not internalized [23].…”
Section: Introductionmentioning
confidence: 74%
“…It has been demonstrated that antibody Fc functionalized pMC’s can bind via Fcγ-RI and Fcγ-RIII onto professional antigenpresenting cells which enables them to activate antigen-specific T cell responses. This can be further enhanced through maturation of the APC with immune-stimulatory agents, such as lipo-poly-saccharide (LPS) [24], Poly (I:C) [32], and anti-CD40 mAb [23,33,34]. These agents cause up-regulation of Fcγ-R and expression of costimulatory molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation